2014
DOI: 10.1007/s00264-014-2563-z
|View full text |Cite
|
Sign up to set email alerts
|

A convertible shoulder system: is it useful in total shoulder arthroplasty revisions?

Abstract: A platform shoulder system allows much easier revisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…6-A and 6-B) 12, 50,203,205,207 . Humeral implant design or improper stem position during the index procedure may prevent retention during revision 12, 203,207,208 . Reported complications at short-term follow-up with platform shoulder systems have included glenoid component failure, infection, brachial plexopathy, and fractures of the acromion and greater tuberosity 12,50,204 .…”
Section: Evolving Trends In Shoulder Arthroplastymentioning
confidence: 99%
“…6-A and 6-B) 12, 50,203,205,207 . Humeral implant design or improper stem position during the index procedure may prevent retention during revision 12, 203,207,208 . Reported complications at short-term follow-up with platform shoulder systems have included glenoid component failure, infection, brachial plexopathy, and fractures of the acromion and greater tuberosity 12,50,204 .…”
Section: Evolving Trends In Shoulder Arthroplastymentioning
confidence: 99%
“… 4 , 5 , 13 , 23 , 26 , 27 , 29 , 31 , 34 , 35 , 36 , 44 , 48 , 49 , 50 , 53 , 54 Nearly all prior reports have suggested that revision RTSA does decrease patient pain and improve patient-reported function. 4 , 5 , 13 , 22 , 23 , 26 , 27 , 29 , 31 , 34 , 35 , 36 , 43 , 44 , 48 , 49 , 50 , 54 However, numerous reports have also noted that final postoperative outcomes after revision RTSA are inferior to those after primary RTSA. 2 , 5 , 9 , 54 In addition, several reports have noted concerning complication rates as high as 50%-69%.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 This last point is particularly relevant as the revision of an anatomic prosthesis for secondary rotator cuff tear or glenoid loosening represents around 20% of the indications for reverse prosthesis. 3,[12][13][14] A short-stem press-fit humeral component with an onlay tray that is convertible from an anatomic to a RSA has recently been designed to avoid these aforementioned complications. The design aims to preserve proximal bone stock and the integrity of tuberosities and also has a decreased neck-shaft angle that provides lateralization and reduces impingement.…”
Section: Introductionmentioning
confidence: 99%